Effects of Bisphenol-A on the morphology and survival of larvae of the sand dollar Dendraster excentricus (Echinodermata, Echinoidea). Issue 3 (3rd July 2021) - Darin, Emily
ABSTRACT: Bisphenol-A (BPA) is an ingredient used in phenol resins, epoxy resins, polyesters and polycarbonate plastics. BPA gets released into the aquatic environment through toxic waste disposal, groundwater, sewage runoff and plastic leaching. When BPA enters aquatic environments, it can affect the development and physiology of marine organisms. This study aimed to understand the effects of relatively low concentrations of BPA on the larvae of the sand dollar Dendraster excentricus . Embryos and larvae were exposed to four treatment solutions (no additives, vehicle control, 50 µg/L BPA, and 500 µg/L BPA) for 7 days. The two BPA treatment concentrations were higher than have usually been detected in coastal marine waters, but lower than those used in most other studies of BPA effects on echinoderm development. After exposure, larval midline body length, postoral arm length, frequency of normal development and survyivorship were measured. Midline body length, frequency of normal development and survivorship all decreased in the presence of BPA, in a dose-dependent manner. Relatively low concentrations of BPA can thus have strong effects on the development of sand dollar larvae.